Osteochondral Autograft: Proceedings of the International Consensus Meeting on Cartilage Repair of the Ankle. (July 2018) - Hurley, Eoghan T.; Murawski, Christopher D.; Paul, Jochen; Marangon, Alberto; Prado, Marcelo P.; Xu, Xiangyang; Hangody, Laszlo; Kennedy, John G.
Background: Treatment guidelines for cartilage lesions of the talus have been based on both low quality and low levels of evidence. Therefore, an international consensus group of experts was convened to collaboratively advance toward consensus opinions on key topics regarding cartilage lesions of the talus. The purpose of this consensus article is to explain the process and delineate the consensus statements derived from this consensus meeting on the use of "osteochondral autograft" for osteochondral lesions of the talus. Methods: Seventy-five international experts in cartilage repair of the ankle representing 25 countries and 1 territory were convened and participated in a process based on the Delphi method of achieving consensus. Questions and statements were drafted within 11 working groups focusing on specific topics within cartilage repair of the ankle, after which a comprehensive literature review was performed and the available evidence for each statement was graded. Discussion and debate occurred in cases where statements were not agreed upon in unanimous fashion within the working groups. A final vote was then held, and the strength of consensus was characterized as follows: consensus, 51% to 74%; strong consensus, 75% to 99%; and unanimous, 100%. Results: A total of 14 statements on osteochondral autograft reached consensus during the 2017 International Consensus Meeting on Cartilage Repair of the Ankle. Two achieved unanimous support, 11 reached strong consensus (greater than 75% agreement), and 1 achieved consensus. All statements reached at least 67% agreement. Conclusions: This international consensus derived from leaders in the field will assist clinicians with osteochondral autograft as a treatment strategy for osteochondral lesions of the talus.